A new mealybug species in the genus Dysmicoccus Ferris (Hemiptera: Coccomorpha: Pseudococcidae), with a key to Chinese species - Zhang, Jiang-Tao; Wang, Xu-Bo; Watson, Gillian W. (Zootaxa, 2023)
A new mealybug species, Dysmicoccus lushanensis Zhang, Wang & Watson sp. n. (Hemiptera: Coccomorpha: Pseudococcidae), collected on the branches of Rhododendron simsii Planch. (Ericaceae) in Jiangxi Province, China, is described and illustrated. It is similar to another species recorded feeding on Rhododendron, D. wistariae (Green 1923), in having small conical dorsal setae and most cerarii containing more than 2 conical setae, but differs from it in having each anal lobe cerarius(C18) with more than two conical setae, and translucent pores present on the hind femur and tibia. The new species also resembles D. finitimus (Williams 1994), which is only known to feed on palms (Arecaceae), in possessing anal lobe cerarius(C18) each with more than 2 conical cerarian setae, but differs in having minute, conical dorsal setae and in lacking translucent pores on the hind coxa. In addition, D. debregeasiae (Green 1922) is recorded from China for the first time. A key to the Chinese species of Dysmicoccus is provided.